2006
DOI: 10.1590/s0103-64402006000100013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity screening of mouthwashes in the pollen tube growth test: safety assessment of recommended dilutions

Abstract: This study investigated whether mouthwash dilutions, recommended by the manufacturers, may contribute to oral mucosa irritation. Twenty frequently used mouthwash brands were examined by the pollen tube growth test, an alternative in vitro method for assessment of the irritating potential of ingredients of cosmetic formulations. The test is based on the photometric quantification of pollen tube growth inhibition. This parameter is expressed by IC 50 values that characterize the cytotoxic potential of a product.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Genetic changes may then cause the development of dysplasia or leukoplakia and, finally, cancer [ 125 , 126 ]. The possibility of damage to the oral mucosa also exists with the use of mouthwashes [ 127 ]. An overview of the effect of ethanol on the oral mucosa is shown in Figure 1 .…”
Section: Reviewmentioning
confidence: 99%
“…Genetic changes may then cause the development of dysplasia or leukoplakia and, finally, cancer [ 125 , 126 ]. The possibility of damage to the oral mucosa also exists with the use of mouthwashes [ 127 ]. An overview of the effect of ethanol on the oral mucosa is shown in Figure 1 .…”
Section: Reviewmentioning
confidence: 99%
“…However, the relative risk was only 0.7 or 0.8 among women who used mouthwashes to conceal food odors or for other reasons. 34 In a case/control study of oral epithelial dysplasia among 127 subjects from two large pathology laboratories, 46 the authors examined eight variables describing mouthwash use and the alcohol content of the products used. The general findings were negative, as were those for all eight variables.…”
Section: Mouthwashes and Oral Cancermentioning
confidence: 99%
“…The conclusion was that there is no relationship between mouthwash use and oral epithelial dysplasia. 46 In a large case/control study with 342 case subjects and 521 control subjects from Puerto Rico with oral cancer, the authors affirmed that they were unable to evaluate the accuracy of the reporting of tobacco, alcohol and mouthwash use. They found no association between mouthwash use and oral cancer.…”
Section: Mouthwashes and Oral Cancermentioning
confidence: 99%
“…Furthermore, a polyethylene glycol derivative of hydrogenated castor oil (PEG-40 Hydrogenated Castor Oil) is a surfactant that can change the barrier properties of human oral mucosa in vitro and in vivo by altering the tight junctions of epithelial cells [ 39 ]. This surfactant, added to the tested gel formulations of the present study, was shown to decrease the viability of a cell line of fibroblasts derived from mice (L929) and human cervical cancer cells (HeLa) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%